Effects of isoinertial or machine-based strength training on performance in tennis players - Canós, Jose; Corbi, Francisco; Colomar, Joshua; Cirer-Sastre, Rafel; Baiget, Ernest (Biology of Sport, 2022)
The objective of this study was to analyze the effects of two 8-week neuromuscular training (NMT) interventions on selected physical indicators in young tennis players. Twenty-four junior male tennis players were assigned to a machine-based (MG) (n = 8), flywheel (FG) (n = 8) or a control training group (CG) (n = 8). Tests at baseline, week 4 and 8 included: countermovement jump (CMJ); speed (S; 5, 10, 15 m); agility (right [AR] and left [AL]); serve velocity (SV) and medicine ball throws (MBT; overhead [O], forehand [FH], backhand [BH]). MG and FG attained large positive effects at week 4 in CMJ, S 10 m; AR, AL and MBT FH only in FG. Regarding inter- to post-test, MG achieved large positive effects in MBT O, FH and both groups in BH. Large negative effects appeared for FG in S 5 and 10 m and AR and AL. Both NMT interventions led to positive effects from baseline to week 4 measures in CMJ, S 5 m, 10 m and agility and at week 8 in MBT. Conducting the same NMT for a longer period of time did not lead to the same improvements and other negative effects in FG appeared. Results indicate that performing these interventions with little exercise variability or load management, especially after technical-tactical sessions, could interpose further beneficial outcomes and initial gains could be impaired.